1997
DOI: 10.1182/blood.v90.6.2217.2217_2217_2233
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Regulates Hematopoietic Progenitor Distribution, Granuloma Formation, and Tumorigenicity

Abstract: CD44 is expressed in various isoforms on numerous cell types and tissues during embryogenesis and in the mature organism. CD44 may also be involved in tumor growth. To study the multiple roles of CD44, we abolished expression of all known isoforms of CD44 in mice by targeting exons encoding the invariant N-terminus region of the molecule. Surprisingly, mice were born in Mendelian ratio without any obvious developmental or neurological deficits. Hematological impairment was evidenced by altered tissue distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 113 publications
4
107
1
Order By: Relevance
“…Comparable paw edema was also observed in CD44 ‐deficient mice (Fig. 4B), which is consistent with a previous study that showed comparable edema in wild‐type and CD44 −/− mice resulting from footpad injection of LCMV (Schmits et al, 1997). Interestingly, mice deficient for both CD44 and LYVE‐1 showed a subtle, but significant, increase in paw swelling compared to wild‐type mice near the peak of edema ( P < 0.05, day 5) (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Comparable paw edema was also observed in CD44 ‐deficient mice (Fig. 4B), which is consistent with a previous study that showed comparable edema in wild‐type and CD44 −/− mice resulting from footpad injection of LCMV (Schmits et al, 1997). Interestingly, mice deficient for both CD44 and LYVE‐1 showed a subtle, but significant, increase in paw swelling compared to wild‐type mice near the peak of edema ( P < 0.05, day 5) (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Because LYVE‐1 has high similarity (43%) to CD44, we tested the hypothesis that CD44 can compensate for the absence of LYVE‐1 (Gale et al, 2007) by generating LYVE‐1 / CD44 double knockout mice. Similar to LYVE‐1 ‐deficient mice, CD44 ‐deficient mice also appear to be indistinguishable from wild‐type mice under normal conditions (Schmits et al, 1997; Protin et al, 1999). Wild‐type, LYVE‐1 −/− , CD44 −/− and LYVE‐1 −/− / CD44 −/− were obtained from mating of double heterozygous mice.…”
Section: Resultsmentioning
confidence: 99%
“…CD44 has long been implicated in the regulation of haematopoietic cell production by the bone marrow 10 , 34 , 35 . The mild phenotype of CD44 knockout mice demonstrates that CD44 is not essential for normal haemopoiesis and is more likely to play a role under situations of stress 9 . However, the precise role for CD44 in haematopoiesis still remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Within the haematopoietic system CD44 plays a role in lymphocyte extravasation across high endothelium and homing to peripheral lymphoid organs 5 , 6 , 7 , 8 . It regulates haematopoietic progenitor cell distribution and mobilization from the bone marrow 9 . It is also believed to mediate the adhesion of haematopoietic cells to stromal components, an interaction important for the survival and differentiation of haematopoietic progenitors in vitro 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies using neutralizing antibodies have revealed certain types of adhesion receptors, such as α4β1/VLA‐4, VCAM‐1, CD44, P‐ and E‐selectins to take part in controlling HSC homing during engraftment and colonization of the hematopoietic organs in the adult mouse (Arroyo, Yang, Rayburn, & Hynes, ; Cao et al, ; Friedrich, Zausch, Sugrue, & Gutierrez‐Ramos, ; Schmits et al, ). Other factors include hyaluronic acid, an alternative receptor for CD44, and osteopontin, which are expressed by ECs and osteoblasts, respectively, and bind to α9β1 and α4β1 integrins (Grassinger et al, ).…”
Section: Hsc Development During Embryogenesismentioning
confidence: 99%